Advokasi Program Jo Kawin Bocah dalam Menekan Perkawaninan Anak di Jawa Tengah - Tri Dwi Daluwati; Amni Zarkasyi Rahman; Dyah Lituhayu (Lembaga Teewan Journal Solutions, 2026)
Child marriage remains a serious social issue in Indonesia, including in Central Java Province. The high rate of child marriage contributes to increased risks of school dropout, poverty, domestic violence, and reproductive health problems. To address this issue, the Central Java Provincial Government, through the Office of Women's Empowerment, Child Protection, Population Control, and Family Planning, initiated the Jo Kawin Bocah Program as a form of advocacy and social movement aimed at reducing child marriage rates. This study aims to analyze the effectiveness of the Jo Kawin Bocah Program advocacy efforts in reducing child marriage rates in Central Java and to identify the supporting and inhibiting factors affecting its implementation. This research employed a descriptive qualitative method, with data collected through interviews, observation, and documentation. The analysis was conducted using Budiani’s program effectiveness theory and the policy advocacy approach developed by Johns Hopkins University. The results indicate that the Jo Kawin Bocah Program has been relatively effective in increasing public awareness of the dangers of child marriage and has contributed to the decline in child marriage rates in Central Java during the 2020–2024 period. The main supporting factors include government regulations, cross-sector collaboration, and the utilization of social media, while the primary inhibiting factors include the persistence of early marriage culture, economic conditions, and limited reproductive health education among adolescents.